2018
DOI: 10.21101/cejph.a4972
|View full text |Cite
|
Sign up to set email alerts
|

A new potential biomarker in early diagnosis of firefighter lung function impairment: dynamic thiol/disulphide homeostasis

Abstract: Objectives: The aim of this study was to investigate the associations between urinary arsenic, oxidative stress, assessed by thiol/disulphide homeostasis, and lung diseases in firefighters. Methods: The study conducted among the municipality-based male firefighters (n = 100) who were admitted to occupational diseases clinic for periodic medical examination. The control group consisted of non-exposed male office workers (n = 50). Urinary arsenic levels, thiol/disulphide homeostasis parameters of participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
2
1
1
Order By: Relevance
“…Median urinary As measured in Turkish firefighters was 15.65 ng/mL, 39 which is substantially higher compared to the median in PROF in our study (6.1 ng/mL). A higher median of As was observed also in Californian firefighters (10.4 ng/mL).…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…Median urinary As measured in Turkish firefighters was 15.65 ng/mL, 39 which is substantially higher compared to the median in PROF in our study (6.1 ng/mL). A higher median of As was observed also in Californian firefighters (10.4 ng/mL).…”
Section: Resultscontrasting
confidence: 64%
“…Median urinary As measured in Turkish firefighters was 15.65 ng/mL, which is substantially higher compared to the median in PROF in our study (6.1 ng/mL). A higher median of As was observed also in Californian firefighters (10.4 ng/mL). , Observed differences might be caused by the natural occurrence of As in the environment and regionally different procedures applied during firefighting and decontamination of the gear.…”
Section: Resultsmentioning
confidence: 92%
“…Gündüzöz et al have shown that firefighters exposed to chronic xenobiotics had abnormal respiratory function tests and chest radiographs, and significantly higher levels of disulfide and disulfide / native thiol. They have emphasized that oxidative stress may play an important role in the pathogenesis of lung injury in these individuals and that early detection of oxidative stress is important (35). Effective use of intensive care beds is extremely important for the provision of hospital services and patient health.…”
Section: Discussionmentioning
confidence: 99%
“…Tiyol disülfid dengesi antioksidan savunmada ve detoksifikasyonda kritik rollere sahiptir [11]. Günümüzde oksidatif stresin birçok kronik hastalığın etiyopatogenezinde rolü olduğu bilinmektedir [10][11][12][13].…”
Section: Introductionunclassified